2007
DOI: 10.1029/2006wr005106
|View full text |Cite
|
Sign up to set email alerts
|

A robust geostatistical approach to contaminant source identification

Abstract: [1] Estimation under model uncertainty remains a practical concern in many scientific and engineering fields. A commonly encountered example in groundwater remediation is the contaminant source identification problem. Like many other inverse problems, contaminant source identification is inherently ill posed and is sensitive to both data and model uncertainties. Model uncertainties, which may be introduced at virtually any stage of a model building process, can adversely affect estimator performance if they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Boano et al (2005) applied a geostatistical approach to determine the release history of a contaminant source at a known location in a river reach. Sun (2007) solved a similar problem in groundwater environment using a robust geostatistical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Boano et al (2005) applied a geostatistical approach to determine the release history of a contaminant source at a known location in a river reach. Sun (2007) solved a similar problem in groundwater environment using a robust geostatistical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive review of source identification methodologies can be found in work by Atmadja and Bagtzoglou (2001b), Michalak and Kitanidis (2004), and Sun et al (2006a). Numerous works related to pollution source identification are available, like least square regression and linear programming with response matrix approach (Gorelick et al 1983), statistical pattern recognition (Datta et al 1989), random walk based backward tracking model (Bagtzoglou et al 1992), nonlinear maximum likelihood estimation (Wagner 1992), nonlinear optimization with embedding technique (Mahar and Datta 1997, 2001, correlation coefficient optimization (Sidauruk et al 1997), backward probabilistic model (Neupauer and Wilson 1999), geostatistical inversion approach (Snodgrass and Kitanidis 1997;Butera and Tanda 2003;Michalak and Kitanidis 2004), Tikhonov regularization (Skaggs and Kabala 1994;Liu and Ball 1999), quasi-reversibility (Skaggs and Kabala 1995;Bagtzoglou and Atmadja 2003), marching-jury backward beam equation (Atmadja and Bagtzoglou 2001a;Bagtzoglou and Atmadja 2003), genetic algorithm based approach (Aral et al 2001;Mahinthakumar and Sayeed 2005;Singh and Datta 2006), artificial neural network approach Datta 2004, 2007;, constrained robust least square approach (Sun et al 2006a, b), robust geostatistical approach (Sun 2007). However, only few studies have incorporated monitoring network within the source identification framework.…”
Section: Notationmentioning
confidence: 99%
“…That is why, a unique solution does not necessarily exist and the solution may be unstable to small changes in the input data (Liu and Ball, 1999). Over the years different methodologies have been proposed for groundwater pollution source identification, e.g., least square regression and linear programming with response matrix approach (Gorelick et al, 1983), statistical pattern recognition (Datta et al, 1989), random walk based backward tracking model (Bagtzoglou et al, 1992), nonlinear maximum likelihood estimation (Wagner, 1992), minimum relative entropy (Woodbury and Ulrych, 1996;Woodbury et al, 1998), nonlinear optimization with embedding technique (Mahar and Datta, 1997, 2001, correlation coefficient optimization (Sidauruk et al, 1997), backward probabilistic model Wilson, 1999, 2005;Neupauer et al, 2000), geostatistical inversion approach (Snodgrass and Kitanidis, 1997;Butera and Tanda, 2003;Michalak and Kitanidis, 2004a, b), Tikhonov regularization (Skaggs and Kabala, 1994;Liu and Ball, 1999), quasireversibility (Skaggs and Kabala, 1995;Bagtzoglou and Atmadja, 2003), marching-jury backward beam equation (Atmadja and Bagtzoglou, 2001a;Bagtzoglou and Atmadja, 2003;Bagtzoglou and Baun, 2005), genetic algorithm based approach (Aral et al, 2001;Mahinthakumar and Sayeed, 2005;Singh and Datta, 2006), artificial neural network approach Datta, 2004, 2007;, constrained robust least square approach (Sun et al, 2006a, b), classical optimization based approach (Datta et al, 2009a, b), robust geostatistical approach (Sun, 2007), inverse particle tracking approach (Bagtzoglou, 2003;Ababou et al, 2010).…”
Section: Introductionmentioning
confidence: 98%